2000
DOI: 10.1073/pnas.011355798
|View full text |Cite
|
Sign up to set email alerts
|

Straightening of bulged RNA by the double-stranded RNA-binding domain from the protein kinase PKR

Abstract: The human interferon-induced protein kinase, PKR, is an antiviral agent that is activated by long stretches of double-stranded (ds)RNA. PKR has an N-terminal dsRNA-binding domain that contains two tandem copies of the dsRNA-binding motif and interacts with dsRNA in a nonsequence-specific fashion. Surprisingly,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 40 publications
9
41
1
Order By: Relevance
“…Straightening, diagrammed in this panel, is supported by independent studies (Zheng and Bevilacqua 2000). Weaker activation of PKR by this RNA as compared to perfect dsRNA, as observed in Figure 4, may be due in part to the thermodynamic penalty for binding to bent RNAs (Zheng and Bevilacqua 2000), although further biophysical studies are needed to confirm this. Panel C presents a model for PKR dimerization and activation by cis 2-chi RNAs, which is also quite similar to panel A involving PKR dimerization.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Straightening, diagrammed in this panel, is supported by independent studies (Zheng and Bevilacqua 2000). Weaker activation of PKR by this RNA as compared to perfect dsRNA, as observed in Figure 4, may be due in part to the thermodynamic penalty for binding to bent RNAs (Zheng and Bevilacqua 2000), although further biophysical studies are needed to confirm this. Panel C presents a model for PKR dimerization and activation by cis 2-chi RNAs, which is also quite similar to panel A involving PKR dimerization.…”
Section: Discussionsupporting
confidence: 55%
“…Panel C presents a model for PKR dimerization and activation by cis 2-chi RNAs, which is also quite similar to panel A involving PKR dimerization. The weakest activation by this RNA, as observed in Figure 4, can be understood by the double penalty of PKR having to bind to bent RNA and having to contend with an RNA-DNA hybrid, for which PKR has poor affinity (Bevilacqua and Cech 1996;Zheng and Bevilacqua 2000). PKR having to contend with this RNA-DNA hybrid region rejects through-space interaction of PKR monomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of a related complex between dsRNA and a dsRBM from a Xenopus RNA-binding protein indicated that the protein binds to one face of a largely undistorted dsRNA helix, with no wrapping around it (Ryter and Schultz 1998). In addition, experiments from our lab showed that the dsRBD binds to RNAs containing bulge defects by straightening of the helix (Zheng and Bevilacqua 2000). Thus, one possibility is that the dsRBD binds to a face of the aptamer without imperfections, extruding any defects away from the binding interface and thereby straightening the helix.…”
Section: Discussionmentioning
confidence: 88%
“…Experiments were similar to previously described (Bevilacqua and Cech 1996;Zheng and Bevilacqua 2000), using excess protein and trace amounts (nM) of radiolabeled RNA, p*RNA. Gel shifts were in the presence of 0.1 mg/mL tRNA competitor.…”
Section: Binding Assaysmentioning
confidence: 99%